An Analysis Cross-Cultural Communication Challenges - Zahira, Dahwa; nadila, fasya; pasaribu, Robiatul adawiyah; Zulfitri (The Explora, 2025)
In today’s globalized world, effective cross-cultural communication has become increasingly essential for fostering collaboration and understanding among diverse populations. This paper explores the multifaceted challenges encountered in cross-cultural interactions, emphasizing the implications of cultural differences in communication styles, values, and social norms. It discusses the significant barriers that arise due to variations in low-context and high-context communication cultures, highlighting how misunderstandings can lead to conflicts and inefficiencies. Additionally, the role of language barriers and the impact of technology on communication dynamics are examined, revealing how digital communication can complicate traditional communication paradigms. Through the analysis of recent case studies and scholarly research, this study identifies key factors contributing to cross-cultural communication challenges and proposes practical strategies to enhance intercultural competence, active listening, and empathy. Ultimately, this analysis aims to provide valuable insights for individuals and organizations navigating the complexities of cross-cultural interactions in an increasingly interconnected world.